Evolution of the Fermi surface of BiTeCl with pressure. (13th June 2017) - VanGennep, D; Jackson, D E; Graf, D; Berger, H; Hamlin, J J
Abstract: We report measurements of Shubnikov–de Haas oscillations in the giant Rashba semiconductor BiTeCl under applied pressures up to ̃2.5 GPa. We observe two distinct oscillation frequencies, corresponding to the Rashba-split inner and outer Fermi surfaces. BiTeCl has a conduction band bottom that is split into two sub-bands due to the strong Rashba coupling, resulting in two spin-polarized conduction bands as well as a Dirac point. Our results suggest that the chemical potential lies above this Dirac point, giving rise to two Fermi surfaces. We use a simple two-band model to understand the pressure dependence of our sample parameters. Comparing our results on BiTeCl to previous results on BiTeI, we observe similar trends in both the chemical potential and the Rashba splitting with pressure.